Comparison of blood gases, hematological and monitorization parameters and determine prognostic importance of selected variables in hypotensive and non-hypotensive calves with sepsis - Amir Naseri; Merve İder (Eurasian Journal of Veterinary Sciences)
Aim: The aim of the present study was to comparison of blood gases, hematological and monitorization parameters in hypotensive and non-hypotensive calves with sepsis and also, determine the probably prognostic variables to prediction mortality. Materials and Methods: Twenty-two calves were met the criteria of sepsis were enrolled in the study. Hypotension was defined as presence of systolic blood pressure (SBP) <90 mmHg and/or mean arterial pressure (MAP) <65mmHg. Results: During study 7 (58%) hypotensive and 4 (40%) non-hypotensive calves died. Clinical findings showed that hypotensive calves had a lower body temperature, SBP and MAP than hypotensive calves. Glucose levels were significantly lower, and RBC and HCT levels were higher in hypotensive calves than non-hypotension calves. Venous pO2 and SO2 were lower and lactate was higher in non-survivor calves than survivor calves. The findings of receiver operating characteristic curve (ROC) showed the area under the curve (AUC) of 0.991 (p=0.000, 95% CI=0.962-1.000), sensitivity of 100% and a specificity of 99% for prediction of mortality at optimum cut off point of 6.7 mmol/L propound the lactate as best prognostic indicator. Conclusion: Mortality rate in hypotensive calves is higher than nonhypotensive calves. Our findings indicated that tissue hypoxia is the strongest determinant of mortality in septic calves. Blood lactate levels with sensitivity of 100% and specificity of %99 at cut-off point of 6.7 mmol/L is the best prognostic indicator to differentiate between survivor and non-survivor calves with sepsis.